Adherence to diet, physical activity and body weight recommendations and breast cancer incidence in the Black Women's Health Study. Issue 12 (19th September 2016) - Nomura, Sarah J. O.; Dash, Chiranjeev; Rosenberg, Lynn; Yu, Jeffrey; Palmer, Julie R.; Adams‐Campbell, Lucile L.
Abstract : Adherence to cancer prevention recommendations has been associated with lower incidence of breast cancer in previous studies, but evidence in African American women is limited. This project evaluated the association between adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) cancer prevention recommendations and breast cancer incidence among African American women. The Black Women's Health Study (analytic cohort = 49, 103) is an ongoing prospective cohort study of African American women, ages 21–69 years at baseline (1995). Adherence scores for seven WCRF/AICR recommendations (adherent = 1, partial adherence = 0.5, non‐adherence = 0) were calculated using questionnaire data and summed for overall (maximum = 7) and diet only (maximum = 5) scores. Associations between baseline and time‐varying adherence scores and breast cancer incidence ( N  = 1, 827 incident cases through 2011) were evaluated using proportional hazards regression. In this cohort, 8.5% adhered >4 recommendations. Adherence at baseline was not associated with breast cancer incidence. Higher overall time‐varying adherence (per 0.5 point increase) was associated with lower breast cancer incidence (HR: 0.90, 95% CI: 0.84–0.96). Adherence to physical activity, sugar beverage and red and processed meat recommendations were also associated with reduced risk. Adherence to the WCRF/AICR recommendations was low and may be associated with lower breast cancer incidence in African American women. Abstract : What's new? Diet, physical activity, and body composition are all potential modifiable risk factors in breast cancer and important targets for primary prevention. But while adherence to cancer prevention recommendations has been associated with lower incidence of breast cancer, evidence in African American women is limited. This study evaluated the association between adherence to cancer prevention recommendations of the World Cancer Research Fund/American Institute for Cancer Research and breast cancer incidence among African American women. The results suggest that work is needed to improve adherence to recommendations among African American women, with the potential to reduce breast cancer incidence through increased adherence.